1997
DOI: 10.1006/viro.1996.8401
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated States of Vesicular Stomatitis Virus P Proteinin Vitroandin Vivo

Abstract: We have previously shown that the phosphoprotein (P) of vesicular stomatitis virus (VSV), New Jersey serotype (PNJ) is phosphorylated by casein kinase II, within the N-terminal domain I (P1 form), whereas the C-terminal domain II is phosphorylated by a protein kinase activity associated with the L protein (P2 form) (D. J. Chattopadhyay and A.K. Banerjee, Cell 49, 407, 1987; A.M. Takacs et al., J. Virol. 66, 5842, 1992). In the present studies, we have mapped the corresponding P1 and P2 phosphorylation sites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
56
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 38 publications
5
56
2
Order By: Relevance
“…The P of the VSV Indiana serotype has been shown to be phosphorylated in two different domains: N-terminal domain I, in which phosphorylation sites were mapped to S60, T62, and S64, and C-terminal domain II, in which phosphorylation sites were mapped to S226 and S227. Since P was shown to be phosphorylated in specific domains involved in regulating transcription in vitro, phosphorylation of P and its role in transcription have been investigated intensively (11)(12)(13)(14)(15)(16)(17)(18). The conclusions derived from these investigations have demonstrated that the phosphorylation of P is important for its functionality in various ways.…”
mentioning
confidence: 99%
“…The P of the VSV Indiana serotype has been shown to be phosphorylated in two different domains: N-terminal domain I, in which phosphorylation sites were mapped to S60, T62, and S64, and C-terminal domain II, in which phosphorylation sites were mapped to S226 and S227. Since P was shown to be phosphorylated in specific domains involved in regulating transcription in vitro, phosphorylation of P and its role in transcription have been investigated intensively (11)(12)(13)(14)(15)(16)(17)(18). The conclusions derived from these investigations have demonstrated that the phosphorylation of P is important for its functionality in various ways.…”
mentioning
confidence: 99%
“…Phosphorylation sites of the VSV P protein have been located to acidic domain I in the N-terminal half and domain II at the C-terminus. Additionally, stepwise phosphorylations at domains I and then II have been proposed for the P protein, in which cellular casein kinase (CK) II and the viral L protein-or nucleocapsidassociated protein kinase activity have been suggested to be involved, respectively (2,3,6). More recently, CK II was shown to be involved in the phosphorylation of domain I, and interconversion of P1 and P2 is a reflection of phosphorylation and dephosphorylation of the phosphate groups in domain I (6).…”
mentioning
confidence: 99%
“…In the presence of cellular casein kinase II, it becomes phosphorylated and functions in transcription in vitro (2,22). By mutational and biochemical studies, the phosphate acceptor sites were mapped to Ser-59 and Ser-61 in P NJ and Ser-60, Thr-62, and Ser-64 in P I (6,53,54). Further studies suggested that the phosphorylation of these residues results in multimerization of the P protein, which in turn facilitates its binding to the L protein for transcription (7,16,17).…”
mentioning
confidence: 99%
“…For P NJ , domain I residues must be phosphorylated prior to the phosphorylation of domain II residues (3), but for P I , domain II residues can be phosphorylated without the prior phosphorylation of domain I residues (6). Since phosphorylation in domain I is essential and sufficient for transcription, it seems that the phosphorylation of domain II may not be involved in transcription (16,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation